2′-Fucosyllactose Is Well Tolerated in a 100% Whey, Partially Hydrolyzed Infant Formula With Bifidobacterium lactis: A Randomized Controlled Trial - Storm, Heidi M. (Glob Pediatr Health, 2019)
Human milk oligosaccharides are important components of breast milk. We evaluated feeding tolerance of the human milk oligosaccharide 2′-fucosyllactose (2′FL) in a 100% whey, partially hydrolyzed infant formula with the probiotic Bifidobacterium animalis ssp lactis strain Bb12 (B lactis; Test) as compared with the same formula without 2′FL (Control) in a randomized controlled trial of healthy infants enrolled at 2 weeks of age (±5 days). After 6 weeks of feeding the assigned formula, the primary outcome of tolerance was assessed using the Infant Gastrointestinal Symptom Questionnaire. Stooling, vomiting, spit-up, crying, and fussing were compared between groups. Seventy-nine infants were enrolled and 63 completed the study per protocol (30 Test, 33 Control). Infant Gastrointestinal Symptom Questionnaire scores were similar between groups (Test 20.9 ± 4.8, Control 20.7 ± 4.3, P = .82). Partially hydrolyzed infant formula with 2′FL and B lactis is tolerated well, as confirmed by a validated multi-symptom index.